Role of leptin in preeclampsia - Devarajachar, Reshma; Rangareddy, Harish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Preeclampsia is one of the common complications of pregnancy and associated with elevated leptin concentrations. In this review the potential sources of leptin are explored and the factors that contribute to maternal increased concentrations of leptin include obesity, insulin resistance and hypoxia. Further research is warranted to understand the role of leptin in pathogenesis of preeclampsia.